The oil palm plantation industry in Malaysia : a study of sustainable management / Sarala Aikanathan - Aikanathan, Sarala (2013)
The palm oil plantation industry in Malaysia has been striving to make production sustainable but land issues have been its consistent bane for the last few decades. The industry stakeholders have set-up various schemes of sustainability for palm oil, but none seem to meet the ever-changing sustainability demands by different consumer groups. Perception of the industry from the media, NGOs and social groups seem to indicate that palm oil will never be sustainable, and thus should reduce its overall production. This study reviewed perception trends with regards to oil palm plantations, and analysed the related variables (economic, social and environmental) that are important for palm oil production in Malaysia. The study also prioritized important variables in measuring sustainability correctly. First, a perception survey of 742 stakeholders was carried out. The analysis shows that within the palm oil industry, stakeholders regard different issues as important for their groups. The perception for the growers and traders/manufactures stated that behavior and perception does not tally with the view of non-Malaysian NGOs, media, literature and third parties. There are obvious gap between what the industry perceives and reality. Lack of measurable variables clearly shows the gaps and the need for sustainability science, especially for the agriculture sector. The industry has set-up its principles and criteria, yet it differs with stakeholder groups, geographical difference and priority in requirements. Sustainable requirement needs to have locality specifications, and not driven by generality or unsubstantiated science or “scientific assumptions”. The perception issues are linked with the lack of measurable variables for sustainability. These variables were considered not important previously. The perception issues and history of the industry are the key determinants now for oil palm's lack of sustainability. In the case of Malaysia, important sustainability criteria would include: greenhouse gas management, good forestry program and communicating sustainable efforts. However, some of these variables are recent in their importance. Second, a simple regression was run to prioritize important variables for sustainability. There were 120 variable across 3 sectors (social, environment and economy) that are important for the palm oil industry. From the perception survey and analysis, two most important variables (dependent variables) were selected: palm oil price per year and total planted area for oil palm in Malaysia (deforested area). Other important variables were harvested area, local crude palm oil (CPO) delivery price, total agriculture land and total arable land. The overall conclusions and implications show that sustainable science is an important element for oil palm management issues. However it is linked with the lack of measurable variables. Perception is an important tool in oil palm sustainability. Lack of measurable variables for sustainability creates unwarranted demands and survey shows palm oil price and total planted area are important variables, whereas total harvested area , agriculture land available, local CPO delivery price and total arable area are the most important variable statistically for Malaysia.